Family and Friend Influence on Urban Dwelling American Indian Adolescent Girl Sexual Risk Behavior - Saftner, Melissa A. (Qual Health Res, 2015)
Previous research with American Indian (AI) adolescent sexual risk behavior primarily focused on reservation dwelling youth despite 70% of AIs living off Native lands. Using grounded theory methodology, I sampled twenty adolescent AI girls via talking circles and interviews to explore the perceptions of AI adolescent girls living in an urban, Midwest area about the influence of family and friends on their sexual behavior. Similar to research with other racial groups, participants cited their family and friends as a major influence. Five unique themes emerged related to family and friend influence. Urban dwelling AI girls rely on their female family members and peers for information related to sex and receive varying messages from their networks of family and friends, which often overlap. AI youth have unique family groups yet have some similarities to other ethnic groups with regards to family and friend relationships that may allow for enhanced intervention development.